Pengaruh Entrepreneurial Marketing Terhadap Marketing Performance Yang Dimediasi Oleh Marketing Assistant - Setiyo Purwanto; Didin Hikmah Perkasa (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This research was conducted on the garment manufacturing industry in Sukabumi, West Java during the COVID-19 pandemic. The purpose of this study was to examine the effect of Entrepreneurial Marketing (EM) on Marketing Performance (MP) with Marketing Assiatant (MA) as a mediation variable. The data in the study consisted of 235 populations with 149 samples. Data analysis in this study used quantitative methods with the SmartPLS 3.2.9 test tool. MA is government assistance help to maintain the sustainability of the SMEs industries, considering that this sector is also a social safety net.